DEIXIS AS A THEMATIC SUCCORING GADGET IN THE OLD MAN AND THE SEA - Dr. Shazia Kousar; M. Salman Tahir; M. Shahzaib Khan (International Journal of Contemporary Issues in Social Sciences, 2023)
Effective linguistic communication is a great challenge for the speakers of any language. The use of deixis makes this communication even more daring due to its vulnerability from fluctuating contexts. The identification of this problem steered the current study to search for the deployment of deixis in the literary masterpiece “The Old Man and the Sea” by Earnest Hemingway. This quantitative research study used the framework of Fillmore and Lyons (1977) for classification of deixis. The data analysis gives evidence that person deixis is the most recurrent deixis in the novel that signposts its feature of character-driven novel. Additionally, the objectivity of narration is demarcated through the use of third person pronoun. The second most widely used deixis is spatial deixis which is represented by vehement use of ‘verbs of motion’ to flaunt the eternal struggle between Man and the forces of Nature. The next deixis in frequency is temporal deixis where the use of present and future tense prove this novel a delineation of determination and resolution of the protagonist to fight for his victory. To conclude, the study claims that the novelist has employed certain deixis strategically and purposefully, rather than accidentally, to push forward the themes of struggle and determination of the protagonist in the novel successfully.